Effect of culture densities on maturation and spawning of the Portuguese oyster (Crassostrea angulata) - Van Vu, Sang; Thanh, Le Tat; Cao, Truong Giang; Van In, Vu (Academia Journal of Biology, 2025)
The Portuguese oyster (Crassostrea angulata) is a mollusc species with many advantages for culture such as fast growth, and high economic importance. However, spat quality and quantity have not met the needs of farmers, leading to unstable annual oyster yield. To improve the spawning efficiency of oyster, we carried out an experiment to evaluate the effect of rearing densities on the maturation and spawning capacities of the Portuguese oyster broodstock, C. angulata. The experiment was evaluated with three rearing densities of 50, 80 and 100 individuals/m3. The results showed that there were no significant changes in the parameters of the environmental factors among three rearing densities (P > 0.05). At a density of 50–80 individuals/m3, survival after 30 days was > 84% and the percentage of oyster matured and spawned was 76−78%. Therefore, this is an essential reference basis for commercial spat production or mass selection program of C. angulata where there are more males and females involved in mating.